Language Assessment : Observation, Examination, Diagnosis And Documentation In Early Childhood Learning - Qurrotul ‘Aini; Nabila Fikri Irfariani (Universitas Muhammadiyah Surabaya, 2020)
The writing of this article aims to provide a format for the development of early childhood language assessment instruments. Which is still a problem for determining the development of early childhood language development assessment instruments. In addition, this article provides procedures for carrying out early childhood assessments that compile observations, examinations, diagnoses and documentation. The basic concept that needs to be emphasized in granting an assessment of age children is by observation using data checklists, anecdotal notes, and video or audio recordings. From the purpose of the assessment there are differences in the time of their implementation. The assessment is analyzed based on the child's language development when speaking in class, talking to his teacher or talking with his fellow peers. Knowledge assessment regarding assessment can also help teachers identify children who might need further development that refers to children's language development.Keywords: Assessment of language development, assessment of observationsbased on analysis of language development individually